(untitled) (KRINOK: JURNAL ARSITEKTUR DAN LINGKUNG BINA, 2024)
Rest areas are facilities that can be used by toll road users to rest when traveling long distances. The many facilities available at the rest area and the beauty on offer mean that toll road users often just stop by. The KM 456 Salatiga Rest Area is one of the most beautiful rest areas on the island of Java, with various facilities and beautiful buildings allowing users to rest while enjoying beautiful views both in terms of nature and buildings. Green architecture is a building planning approach that is created to minimize various harmful effects on health, safety, human health and the environment. In implementing Green Architecture in the KM 456 Salatiga Rest Area, the building has an Eco design, environmentally friendly architecture and natural architecture. The influence of implementing green architecture in the KM 456 Salatiga rest area provides a deeper understanding of buildings that are environmentally friendly and do not damage the environment or the natural surroundings.